Mapping solid waste governance modes in a Mexican municipality - Grecia Cruz-Paz; Darío Navarrete Gutiérrez; Claudia María Monzón Alvarado; Alejandro Espinoza-Tenorio; Hugo Alejandro Nájera-Aguilar (Sustainable Environment, 2023)
ABSTRACTHuman decisions and modes of organization can be analyzed according to their rationale, which can be based on hierarchies, markets, or networks. This classification is known as governance modes. This article addresses municipal solid waste (MSW) governance inside and outside protected areas based on the Sepultura Biosphere Reserve (REBISE) case in Chiapas, Mexico. We conducted semi-structured interviews and a content analysis of laws and municipal regulations to identify the stakeholders and institutions that operate at community and municipal levels. Our research is a first effort to analyze the modes of MSW governance and offers a spatially explicit classification to reveal the spatial differences in how MSW is governed. The populations close to the capital city and the main roads have a multiplicity of mechanisms and modes of MSW governance, which contrasts with distant communities located within the REBISE. This work illustrates the gaps where municipal authorities are unable to fulfill their obligations and the potential of market and collaborative mechanisms. Characterizing governance modes through spatially explicit thematic maps reveals the interactions between stakeholders and formal and informal institutions, which could contribute to territorial planning toward more effective MSW governance.